A hybrid method to update stress for perfect von-Mises plasticity coupled with Lemaitre damage mechanics. Issue 2 (27th August 2019) - Tavoosi, Maliheh; Sharifian, Mehrdad; Sharifian, Mehrzad
Abstract : Purpose: The purpose of this paper is to suggest a robust hybrid method for updating the stress and plastic internal variables in plasticity considering damage mechanics. Design/methodology/approach: By benefiting the properties of the well-known explicit and implicit integrations, a new mixed method is derived. In fact, the advantages of the mentioned techniques are used to achieve an efficient integration. Findings: The numerical studies demonstrate the high precision and robustness of the suggested algorithm. Research limitations: The perfect von-Mises plasticity together with Lemaitre damage model is considered within the realm of small deformations. Practical implications: Updating stress and plastic internal variables are of utmost importance in elastoplastic analyses of structures. The accuracy and efficiency of stress-updating methods significantly affect the final outcomes of nonlinear analyses. Originality/value: The idea which is used to derive the hybrid method leads to an efficient integration method for updating the constitutive equations of the damage mechanics.